Text Messages to Improve Medication Adherence and Secondary Prevention After Acute Coronary Syndrome: The TEXTMEDS Randomized Clinical Trial. Issue 19 (10th May 2022) - Chow, Clara K.; Klimis, Harry; Thiagalingam, Aravinda; Redfern, Julie; Hillis, Graham S.; Brieger, David; Atherton, John; Bhindi, Ravinay; Chew, Derek P.; Collins, Nicholas; Andrew Fitzpatrick, Michael; Juergens, Craig; et al.
Abstract : Background: TEXTMEDS (Text Messages to Improve Medication Adherence and Secondary Prevention After Acute Coronary Syndrome) examined the effects of text message–delivered cardiac education and support on medication adherence after an acute coronary syndrome. Methods: TEXTMEDS was a single-blind, multicenter, randomized controlled trial of patients after acute coronary syndrome. The control group received usual care (secondary prevention as determined by the treating clinician); the intervention group also received multiple motivational and supportive weekly text messages on medications and healthy lifestyle with the opportunity for 2-way communication (text or telephone). The primary end point of self-reported medication adherence was the percentage of patients who were adherent, defined as >80% adherence to each of up to 5 indicated cardioprotective medications, at both 6 and 12 months. Results: A total of 1424 patients (mean age, 58 years [SD, 11]; 79% male) were randomized from 18 Australian public teaching hospitals. There was no significant difference in the primary end point of self-reported medication adherence between the intervention and control groups (relative risk, 0.93 [95% CI, 0.84–1.03]; P =0.15). There was no difference between intervention and control groups at 12 months in adherence to individual medications (aspirin, 96% vs 96%; β-blocker, 84% vs 84%; angiotensin-converting enzyme inhibitor/angiotensin receptor blocker, 77% vs 80%; statin, 95% vs 95%; second antiplatelet, 84% vs 84% [all P >0.05]), systolic blood pressure (130 vs 129 mm Hg; P =0.26), low-density lipoprotein cholesterol (2.0 vs 1.9 mmol/L; P =0.34), smoking ( P =0.59), or exercising regularly (71% vs 68%; P =0.52). There were small differences in lifestyle risk factors in favor of intervention on body mass index <25 kg/m 2 (21% vs 18%; P =0.01), eating ≥5 servings per day of vegetables (9% vs 5%; P =0.03), and eating ≥2 servings per day of fruit (44% vs 39%; P =0.01). Conclusions: A text message–based program had no effect on medical adherence but small effects on lifestyle risk factors. Registration: URL: https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=364448 ; Unique identifier: ANZCTR ACTRN12613000793718.